2017
DOI: 10.1242/dev.145318
|View full text |Cite
|
Sign up to set email alerts
|

Genetic redundancy of GATA factors in extraembryonic trophoblast lineage ensures progression of both pre and postimplantation mammalian development

Abstract: GATA transcription factors are implicated in establishing cell fate during mammalian development. In early mammalian embryos, GATA3 is selectively expressed in the extraembryonic trophoblast lineage and regulates gene expression to promote trophoblast fate. However, trophoblast-specific GATA3 function is dispensable for early mammalian development. Here, using dual conditional knockout mice, we show that genetic redundancy of Gata3 with paralog Gata2 in trophoblast progenitors ensures the successful progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
100
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 82 publications
4
100
0
Order By: Relevance
“…In the mouse placenta, Dlx3 expression is controlled by GATA2 and −3 transcription factors (Home, et al 2017). These transcription factors are also regulators of mouse trophoblast differentiation (Home, et al 2009, Ralston, et al 2010, Ray, et al 2009).…”
Section: Transcription Factors Regulating Ifnt Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse placenta, Dlx3 expression is controlled by GATA2 and −3 transcription factors (Home, et al 2017). These transcription factors are also regulators of mouse trophoblast differentiation (Home, et al 2009, Ralston, et al 2010, Ray, et al 2009).…”
Section: Transcription Factors Regulating Ifnt Expressionmentioning
confidence: 99%
“…Clearly, further studies are needed to address whether GATA factors directly interact with the IFNT regulatory regions or even modulate IFNT promoter activity in trophoblast. Another possibility is that they act indirectly through other GATA2 and −3 regulated genes, such as DLX3 (Home, et al 2017). …”
Section: Transcription Factors Regulating Ifnt Expressionmentioning
confidence: 99%
“…Using the promoter from a specific gene or a chimeric DNA construct to direct Cre expression in specific cells is the key component of the Cre/loxP system. Although several promoters have been used to target transgene expression in trophoblast lineages, to our knowledge very few studies have been conducted using inducible Cre/loxP specifically for placental research . Furthermore, in both of these models, broadly expressed Cre transgenic animals were utilized, complicating the interpretation of the results.…”
Section: Introductionmentioning
confidence: 99%
“…They are implicated in the regulation of the expression of several trophoblast-specific genes, including prolactin hormone Placental lactogen I (Prl3d1, Pl1) and the angiogenic factor Proliferin (Prl2c2, Plf), which play an essential role in the neovascularization of the placenta (14,15). Recently we demonstrated that simultaneous knockout of both Gata2 and Gata3 in trophoblast lineage severely affects placental development (16). Also, the double gene knock-out resulted in significant developmental defects in the embryo proper leading to very early embryonic lethality (16).…”
Section: Introductionmentioning
confidence: 99%